Implementation Of Green Economy Through Green Financing For Tofu Smes In Sumbermulyo Village - Gangga, Famung; Sa’adah, Lailatus (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the implementation of green economy through green financing in tofu MSMEs in Sumbermulyo Village, Jogoroto District. The focus is on the role of green financing in supporting small business sustainability. Methodology: A descriptive qualitative approach was used with participatory observation techniques and semi-structured interviews with 10 MSME players. Results: It was found that 50% of the actors have implemented green economy principles, such as utilizing waste as animal feed. However, only 10% were aware of green financing schemes, due to lack of socialization and access to information. Findings: The practice of the 3Rs (Reduce, Reuse, Recycle) has had a positive impact in reducing pollution, although challenges such as waste odor and limited capital still hinder. Originality: This study is one of the first to discuss green financing in the context of rural tofu MSMEs, by offering an environmentally friendly community financing model. Its contribution lies in the contextual analysis of the rarely researched local food sector. Conclusion: The integration of green economy and green financing in tofu MSMEs has the potential to promote sustainability, but requires institutional support. Type of paper: Empirical research Paper.